2011
DOI: 10.1038/emboj.2010.353
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42-dependent formation of the ZO-1/MRCKβ complex at the leading edge controls cell migration

Abstract: Zonula occludens (ZO)-1 is a multi-domain scaffold protein known to have critical roles in the establishment of cell-cell adhesions and the maintenance of stable tissue structures through the targeting, anchoring, and clustering of transmembrane adhesion molecules and cytoskeletal proteins. Here, we report that ZO-1 directly binds to MRCKb, a Cdc42 effector kinase that modulates cell protrusion and migration, at the leading edge of migrating cells. Structural studies reveal that the binding of a b hairpin from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 62 publications
6
59
0
1
Order By: Relevance
“…Treatment for 30 minutes with inhibitors at concentrations near their EC 50 on Western blots showed that 0.5 μM Y27632 effectively reduced stress-fibre associated pMLC staining but had little effect on cortical pMLC, in agreement with previous reports showing that ROCK principally phosphorylates cytoplasmic MLC [10]. In contrast, application of 0.5 μM BDP5290 lessened both cytoplasmic and cortical pMLC levels, which is consistent with previous reports showing that an important site of MRCK function is at cortical cytoskeletal structures proximal to the plasma membrane [21,22].…”
Section: Mrck Inhibition In Cellssupporting
confidence: 82%
“…Treatment for 30 minutes with inhibitors at concentrations near their EC 50 on Western blots showed that 0.5 μM Y27632 effectively reduced stress-fibre associated pMLC staining but had little effect on cortical pMLC, in agreement with previous reports showing that ROCK principally phosphorylates cytoplasmic MLC [10]. In contrast, application of 0.5 μM BDP5290 lessened both cytoplasmic and cortical pMLC levels, which is consistent with previous reports showing that an important site of MRCK function is at cortical cytoskeletal structures proximal to the plasma membrane [21,22].…”
Section: Mrck Inhibition In Cellssupporting
confidence: 82%
“…ZO-1 is a multiple domain scaffold protein with a reported role in cell to cell adhesion, maintenance of tissue structure and hence modulates angiogenesis and cellular migration during the tissue remodeling and repair. 22 The binding of miR-191 to 3′untranslated region of ZO-1 transcript was confirmed by reduced luciferase reporter activity after miR-191 overexpression ( Figure 4D). In line, ZO-1 knockdown showed a similar phenotype as that of miR-191 overexpression in dermal cells.…”
Section: Paracrine Functional Effects Of Circulating Diabetic Mirnasmentioning
confidence: 77%
“…31) IEC-6 cells transfected with miR-191a inhibitor moved more quickly compared with cells without transfection before TNF-α (Fig. 2), ZO-1 is the target gene of miR-191a, ZO-1 protein actively regulates cell migration, the knockdown of ZO-1 greatly inhibits wound- induced cell migration and the restoration of ZO-1 improves cell motility injured by knockdown of ZO-1, 32) In addition, we show that baicalin inhibits TNF-α-induced ZO-1 depletion by down-regulating miR-191a, miR-191a inhibition enhanced the TNF-α-reduced IEC-6 cells migration improved by baicalin, to sum up, we can reason that baicalin protect against TNF-α-reduced cell migration in IEC-6 cells, and keep the integrity of intestinal barrier with a mechanism involving suppression of miR-191a expression.…”
Section: Discussionmentioning
confidence: 96%